Engineering of Superhydrophobic Materials: Applications and Prospects in Oil-Water Separation Technology - Silvia Devi Eka Putri; Eka Cahya Muliawati (Science Journal Get Press, 2025)
The rapid growth of industries like petrochemical processing, offshore drilling, transportation, and metallurgy has increased oily wastewater and oil spills, threatening ecosystems and human health. Traditional oil-water separation methods often struggle with low efficiency and poor stability, especially against stable emulsions. This study investigates superhydrophobic materials fabricated via dip-coating on stainless steel mesh, electrospinning of PVDF membranes, and chemical etching of aluminum surfaces. All materials showed excellent water repellency with contact angles over 150°, achieving oil-water separation efficiencies above 97% for various oils. The dip-coated mesh achieved the highest flux and separation efficiency, while the electrospun membrane offered enhanced chemical resistance and durability. Despite promising results, challenges remain including mechanical abrasion resistance, environmental concerns over hydrophobic coatings, and scalability for industrial use. Future research should focus on eco-friendly, self-healing, and stimulus-responsive coatings to improve durability and environmental safety, advancing the practical application of superhydrophobic materials in wastewater treatment and oil spill remediation.